2012
DOI: 10.1007/s00264-012-1622-6
|View full text |Cite
|
Sign up to set email alerts
|

The techniques of soft tissue release and true socket reconstruction in total hip arthroplasty for patients with severe developmental dysplasia of the hip

Abstract: Purpose Total hip arthroplasty (THA) is an effective procedure for developmental dysplasia of the hip (DDH); however, it is sometimes difficult to complete for severe cases because of femoral head dislocation, dysplasia of the acetabulum and the femur, disparity in limb length, soft tissue contraction, and muscular atrophy. We aimed at exploring the efficiency of the techniques of release and balance of soft tissues and reconstruction of true socket THA for patients with severe DDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…And finally, the soft tissue balance is of great importance (especially the need to preserve the continuity of abductors) to maximise postoperative functional result. 8,9 Various techniques have been described in the literature (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…And finally, the soft tissue balance is of great importance (especially the need to preserve the continuity of abductors) to maximise postoperative functional result. 8,9 Various techniques have been described in the literature (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…For some time we performed THA [26] in the high dislocated hip using extensive soft tissue release without femur osteotomy, as described by Wu et al [24]. We found that this technique for hip reduction was very difficult and the risk of nerve injury was high.…”
Section: Discussionmentioning
confidence: 99%
“…The combined anteversion of all patients were set under 55° to prevent post‐surgery dislocation. Specific soft tissue release can vary widely and relate to the hip capsule, iliotibial tract, part of gluteus, the adductor, iliopsoas muscle, sartorius muscle, and rectus femoris.…”
Section: Methodsmentioning
confidence: 99%